Palingenesia e modos do cuidado de si no surgimento do discurso espírita - Faria, Letícia Tavares de (2018)
This thesis sought to understand the discourses of Spiritism at the time of its emergence in the nineteenth century. How was this object of knowledge formed, and what knowledge did it mobilize to establish itself resulting in powers, subjecting individuals to a kind of self-care in modernity. Has it been from devices such as palingenesia, or the theory of successive lives, the so-called reincarnation, which was able to establish relationships that would subjectivate the subject for self-care? Spiritism pleads for itself, as a teaching of the Superior Spirits, the status of science and philosophy. It is developed from a methodology used according to nineteenth-century science, such as observation of phenomena and deduction of general laws, publication of results. Establishes knowledge, network of relationships with the individual, indicates the way to modern ascesis. It reflects the discourse of self-care for self-government to be happy in this life and in the next lives, not as proselytism but pleading that its truths are a path of happiness, what must be followed is a project based on natural laws. It proposes relationships and techniques of self to subjectivate the way in which the subject must build his life in the relation with the other. This work investigated this set of values from Foucault, through the primary and secondary reading of his work on ethics and the construction of an aesthetic of himself. Also the work of historians of religions and societies was fundamental to analyze the networks of relations between the discourses on an immortal man, an individual with great responsibility about himself, a subject of self care. The corpus analyzed was the Third Book - Moral Laws, from The Book of Spirits. As a methodology, I investigated the texts written by Allan Kardec and sought their relations with the nineteenth century and their social movements, economic relations and tensions established by capitalism, the proletariat and the bourgeoisie; the departure of the church, the rise of Protestant sects marked by psychic phenomena and the full range of ideas around spiritual manifestations. These relationships led to the understanding of self-care in a rule drawn in modernity.